2009
DOI: 10.1371/journal.pone.0005859
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical Analysis of Etoposide Induced DNA Breaks

Abstract: BackgroundEtoposide is a cancer drug that induces strand breaks in cellular DNA by inhibiting topoisomerase II (topoII) religation of cleaved DNA molecules. Although DNA cleavage by topoisomerase II always produces topoisomerase II-linked DNA double-strand breaks (DSBs), the action of etoposide also results in single-strand breaks (SSBs), since religation of the two strands are independently inhibited by etoposide. In addition, recent studies indicate that topoisomerase II-linked DSBs remain undetected unless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 45 publications
5
59
1
2
Order By: Relevance
“…The detection of cleavage at precise sites also found in vitro and at translocation breakpoint hotspots, as well as local base preferences for cleavage mirroring those in vitro, gave validation to our assay. Also, the 1.3%-3.4% TOP2A DNA DSBs that we found are consistent with prior studies (Zechiedrich et al 1989;Muslimovic et al 2009). Overall, our methodology achieved the genome-wide identification of TOP2A cleavage sites not previously accomplished.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The detection of cleavage at precise sites also found in vitro and at translocation breakpoint hotspots, as well as local base preferences for cleavage mirroring those in vitro, gave validation to our assay. Also, the 1.3%-3.4% TOP2A DNA DSBs that we found are consistent with prior studies (Zechiedrich et al 1989;Muslimovic et al 2009). Overall, our methodology achieved the genome-wide identification of TOP2A cleavage sites not previously accomplished.…”
Section: Discussionsupporting
confidence: 93%
“…Etoposide occupancy at both scissile bonds is required for DSBs, and most breaks formed at concentrations relevant to chemotherapy are SSNs (Bromberg et al 2003). Consistent with reports in which the vast majority of detected TOP2 cleavage events were SSNs (Bromberg et al 2003;Muslimovic et al 2009), we found 1.3%-3.4% of TOP2A cleavage events were DSBs and the remainder were SSNs (Supplemental Table S1; Supplemental Fig. S2).…”
Section: Top2a Cleavage Events Are Ssns More Often Than Dsbssupporting
confidence: 90%
See 1 more Smart Citation
“…Single-stranded DNA damage is therefore not very toxic. As an example, over 100 000 hydrogen peroxide-induced single-stranded DNA damage is required to affect the viability of a human cell (Muslimovic, Nystrom et al 2009). However, template-directed repair is not possible when both DNA strands within 10-20 bp are damaged, called clustered DNA damage (Fig.…”
Section: Radiation-induced Dna Damagementioning
confidence: 99%
“…Several reports indicate that each IR-induced gamma-H2AX focus represents a single DSB, at least in G1 cells (Sedelnikova, Rogakou et al 2002;Pilch, Sedelnikova et al 2003;Rothkamm and Lobrich 2003). The level of gamma-H2AX induced by different drugs and radiation is closely correlated to the level of cell death (Banath and Olive 2003;Muslimovic, Nystrom et al 2009). This indicates that measurement of gamma-H2AX in patient cells will be a biologically important marker for the induction of DSBs and toxicity following chemotherapy and radiotherapy.…”
Section: Dsb Response and H2ax Phosphorylationmentioning
confidence: 99%